Self-Adaptive Extrapolated Gauss-Seidel Iterative Methods (Journal of Mathematical Study, 2018)
In this paper, we consider a self-adaptive extrapolated Gauss-Seidel methodfor solving the Hermitian positive definite linear systems. Based on optimization models,self-adaptive optimal factor is given. Moreover, we prove the convergence of theself-adaptive extrapolated Gauss-Seidel method without any constraints on optimalfactor. Finally, the numerical examples show that the self-adaptive extrapolated Gauss-Seidel method is effective and practical in iteration number.